Sarcastic Reasoning in Al-Jahiz’s Message of Tarbee and Tadweer and Ibn Zaidoon’s Sarcastic Message: The Controversy of Persuasion and Refrain - Shtiat, Fuad Feyyad; Al-Hazaimeh, Farouk Ahmad Turky; Al-Zu’bi, Basil Faisal Sa’ed (LANGUAGE ART, 2022)
The research deals with the subject of mock controversy in the letters of (al-Tarbiya & Tadwir) by Al-Jahiz and the comic message of Ibn Zaydun, and the relationship between that controversy and its political address, so discusses the role of irony in persuading the recipient of what the two writers propose based on the place governed by competition between the creator and the central figure in the two discourses and its relationship to the political role of all of them, and the research analyzes. One of the results obtained from this research is that: those two texts are the first and basic texts that exist in the basis of humorous Arabic literature. This basis is the same as in ancient Arabic narration through treatises and various other literary items such as maqamah, anecdotes, and folk stories.The tools of rhetorical irony that outlive the two texts and the receptacles of the language in which they are covered.